Departmental Exploration: West Pakistan - Khan, F. A. (1964)
Sites in the Karachi Pir Mango, Orangi, Lyari River Area, Nel Bazar Site – Gujjo – Deh Mari Sabra – Judeir-jo-daro – Pirak Mound – Bolan Pass Area: Dranjan Site – Rindli Mound – North Baluchistan and Kalat Sites — Ispelinji Valley: Ispelinji Mounds; Sardar Khel Mound – Sakesar Site: Salt Range.